Abundance of cysteine endopeptidase dionain in digestive fluid of Venus flytrap (Dionaea muscipula Ellis) is regulated by different stimuli from prey through jasmonates - Libiaková, Michaela; Floková, Kristýna; Novák, Ondřej; Slováková, L'udmila; Pavlovič, Andrej (PLoS One, 2014)
The trap of the carnivorous plant Venus flytrap (Dionaea muscipula) catches prey by very rapid closure of its modified leaves. After the rapid closure secures the prey, repeated mechanical stimulation of trigger hairs by struggling prey and the generation of action potentials (APs) result in secretion of digestive fluid. Once the prey's movement stops, the secretion is maintained by chemical stimuli released from digested prey. We investigated the effect of mechanical and chemical stimulation (NH4Cl, KH2PO4, further N(Cl) and P(K) stimulation) on enzyme activities in digestive fluid. Activities of β-D-glucosidases and N-acetyl-β-D-glucosaminidases were not detected. Acid phosphatase activity was higher in N(Cl) stimulated traps while proteolytic activity was higher in both chemically induced traps in comparison to mechanical stimulation. This is in accordance with higher abundance of recently described enzyme cysteine endopeptidase dionain in digestive fluid of chemically induced traps. Mechanical stimulation induced high levels of cis-12-oxophytodienoic acid (cis-OPDA) but jasmonic acid (JA) and its isoleucine conjugate (JA-Ile) accumulated to higher level after chemical stimulation. The concentration of indole-3-acetic acid (IAA), salicylic acid (SA) and abscisic acid (ABA) did not change significantly. The external application of JA bypassed the mechanical and chemical stimulation and induced a high abundance of dionain and proteolytic activity in digestive fluid. These results document the role of jasmonates in regulation of proteolytic activity in response to different stimuli from captured prey. The double trigger mechanism in protein digestion is proposed.
Keywords: buněčný převod mechanických signálů; Cysteine Endopeptidases; listy rostlin; rostlinné proteiny; Plant Leaves; Plant Growth Regulators; oxylipiny; regulátory růstu rostlin; Cyclopentanes; Mechanotransduction, Cellular; Plant Proteins; cysteinové endopeptidasy; Droseraceae; cyklopentany; Oxylipins